1995
DOI: 10.1073/pnas.92.22.10099
|View full text |Cite
|
Sign up to set email alerts
|

Efficient gene transfer into human hepatocytes by baculovirus vectors.

Abstract: Viral vectors are the most efficient tools for gene delivery, and the search for tissue-specific infecting viruses is important for the development of in vivo gene therapy strategies. The baculovirus Autographa californica nuclear polyhedrosis virus is widely used as a vector for expression of foreign genes in insect cells, and its host specificity is supposed to be restricted to arthropods. Here we demonstrate that recombinant A. californica nuclear polyhedrosis virus is efficiently taken up by human hepatocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
373
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 453 publications
(391 citation statements)
references
References 40 publications
(22 reference statements)
17
373
0
1
Order By: Relevance
“…Many different gene delivery methods are available including cationic lipid-based DNA transfection [44][45][46][47][48][49] and retroviral and adenoviral gene transfer vectors; [50][51][52][53][54][55] however, the use of these methods for hepatocytes has not been effective because hepatocytes do not divide, are highly susceptible to toxicity, and transfection efficiencies in hepatocytes are extremely low (HC Isom, unpublished data). 11 Previous studies have reported baculovirus-mediated gene delivery to primary hepatocytes. 6,11,12 In these studies, baculovirus-mediated gene delivery was highly efficient (470%) and homogeneous.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many different gene delivery methods are available including cationic lipid-based DNA transfection [44][45][46][47][48][49] and retroviral and adenoviral gene transfer vectors; [50][51][52][53][54][55] however, the use of these methods for hepatocytes has not been effective because hepatocytes do not divide, are highly susceptible to toxicity, and transfection efficiencies in hepatocytes are extremely low (HC Isom, unpublished data). 11 Previous studies have reported baculovirus-mediated gene delivery to primary hepatocytes. 6,11,12 In these studies, baculovirus-mediated gene delivery was highly efficient (470%) and homogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…11 Previous studies have reported baculovirus-mediated gene delivery to primary hepatocytes. 6,11,12 In these studies, baculovirus-mediated gene delivery was highly efficient (470%) and homogeneous. However, these studies were carried out using cells in short-term culture conditions and as such, the hepatocytes were poorly differentiated and do not have intact paracellular junctions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To study this hypothesis, the transduction efficiency of HeLa, SKOV-3, BT4C, HepG2, EAHY and 293T cells was determined with the VSV-GED virus and control virus using MOIs ranging from 10 to 1000. 20,21 On the contrary, EAHY cell line has been reported to be poorly susceptible to baculovirus transduction. 22 Transduction efficiency of HeLa, SKOV-3, BT4C and 293T settles between HepG2 and EAHY.…”
Section: Improved Transduction Efficiency In Vitromentioning
confidence: 99%
“…16 Early studies showed that baculovirus vectors could efficiently transduce human hepatocyte cell lines and explanted human liver tissue. 17,18 Subsequently, it was demonstrated that baculovirus vectors could enter a broader variety of human cell types. [19][20][21] We set out to determine whether gp64 could be used to pseudotype other viral vectors and confer high infectivity in cells of hepatic origin, which are primary targets for many genetherapy applications.…”
Section: Introductionmentioning
confidence: 99%